Pelatihan desain media interaktif pada pembelajaran daring bagi dosen pendidikan biologi - Samsuri, Taufik; Muliadi, Agus; Muhali, Muhali; Asy’ari, Muhammad; Prayogi, Saiful; Hunaepi, Hunaepi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2020)
Online learning is a national policy as a strategic step to prevent the spread of the Covid-19 virus. The quality of the learning media used by lecturers is to influence the effectiveness of online learning. Therefore, training is needed to strengthen lecturers' skills in developing interactive media effective in online learning. This community service aims to improve the biology education lecturers' knowledge and skills regarding interactive media design in online learning. Participants of this activity were 27 Lecturers of Biology Education at FSTT Mandalika University of Education. The training activity is carried out in three stages, namely (1) Preparation, (2) Implementation, (3) Reflection / Evaluation. Training activities are held online / webinar on Saturday / 25 July 2020 at 07.00-12.00 WITA with a series of events, namely opening, remarks from the Head of the Biology Education Study Program, delivery of training materials, discussions, conveying impressions and messages. The training activities were carried out well, even though there were some shortcomings. This is supported by the participants' messages at the end of the activity, namely (1) 100% of the training participants gave positive responses such as feeling happy, enthusiastic, enthusiastic, and helped by the holding of this training activity; (2) 75% of participants gave suggestions so that similar training activities could be carried out periodically at the beginning of preparation for each semester. In the end, the participants have the knowledge and skills in designing interactive media in online learning